Short S=O center dot center dot center dot C=O contacts associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate in their inclusion complexes - Manoj, Kochunnoonny; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Crystal Growth & Design, 2005)
Diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate are linked via short S=O&BULL;&BULL;&BULL; C=O contacts ranging from 2.890 to 3.140 &ANGS; (sum of the van der Waals radii of O and C atoms 3.22 &ANGS;) in all the inclusion complexes formed with organic guest solvents having a C2 symmetry. Although a search for S= O&BULL;&BULL;&BULL; C=O interactions in the CSD showed a sizable number of structures, this communication recognizes its significance for the first time in the formation of molecular assemblies. In all the crystals in the present study except the solvent-free form, the S=O bond points almost perpendicularly to the Csp2 atom of the C=O group. This was also the most frequently observed geometrical approach in CSD analysis. The solvent-free form shows dimer formation via C-H&BULL;&BULL;&BULL; O interaction, which has longer S=O&BULL;&BULL;&BULL; C=O contacts.

Subtle crossover from C-H center dot center dot center dot O to S=O center dot center dot center dot C=O short contacts in the association of diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate upon format - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystal Growth & Design, 2006)
Diastereomers of 2,4(6)- di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate associate via weak interactions to form ``head-to-head'' dimers in their crystals. Molecular association through C-H center dot center dot center dot O short contacts do not leave any void for the guest inclusion, while association through S=O center dot center dot center dot C=O bridging produces pseudopolymorphs. Three crystalline modifications are observed for the title compound: form I, monoclinic P2(1), without any guest solvent, and solvated forms II and III, that belong to monoclinic space groups P2(1) and C2, respectively. A majority of solvates, which include pyridine, dichloromethane, benzene, tetrahydrofuran, and cyclohexanone as guests, belong to form III. All these guests have 2-fold symmetry axes ( C2) with their electron count within 40-62 electrons; guest selectivity experiments indicate that planar aromatic guests ( pyridine, benzene) bind better to the host molecules as compared to nonplanar guests ( dioxane, cyclohexanone). The molecular packing that is created thorough channels in the crystal ( avoiding interpenetration of the layers) are of interest because of their potential application in molecular separation by forming selective inclusions. The diastereomeric association via S=O center dot center dot center dot C=O dipolar short contacts, a consistent feature observed in all the solvates, is thought to have relevance in the binding of sulfonyl drugs to the C=O moieties of the receptor proteins.

Syntheses, characterisation and vapour pressure of metallo-organic titanium precursor for MOCVD applications - Arockiasamy, S.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mallika, C.; Nagaraja, K. S. (Inorganica Chimica Acta, 2010)
Metallo-organic complexes of titanium such as [Ti(bzac)(2)(O(i)Pr)(2)] (1) and [Ti(bzac)(2)en(O(i)Pr)(2)] (2) were synthesised using 1-phenyl-1,3-butanedione (bzac) and the Schiff's base ligand N, N0-ethylene-bis(1-phenyl-1,3-butanediimine) [(bzac)(2)en]. A novel ligand 1-phenyl-3-N-(2-hydroxy-2-methylethylimino)-1-butanone (bzac1a2pol, 3) synthesised by condensing benzoylacetone (bzac) with 1-amino-2-propanol (1a2pol) was used in the synthesis of the complex bis(1-phenyl-3-N-(2-hydroxy-2-methylethylimino)-1-butanoato)titanium (IV), [Ti(bzac1a2pol)(2), 4]. These complexes were synthesised by replacing the isopropoxy group (O(i)Pr) of titanium tetra-isopropoxide, Ti(O(i)Pr)(4) by the appropriate ligands. Complexes 1, 2 and 4 were characterised for their volatility/thermal stability using TG/DTA and complex 4 was found to be volatile giving a residue of similar to 5.0% (TG) at 377 degrees C and similar to 3.0% (reduced pressure, 1 mbar) at 285 degrees C. Ligand 3 and its Ti complex 4 were characterised by (1)H NMR, (13)C NMR, elemental analysis, mass spectrometry and single crystal XRD. A value of 164.2 +/- 5.2 kJ mol(-1) for the standard enthalpy of sublimation (Delta H(sub)(0)) was evaluated for 4 from its vapour pressure. (C) 2010 Elsevier B. V. All rights reserved.
Keywords: MOCVD; Single crystal; Syntheses; Ti complexes; Vapour pressures; Volatile complexes

Solvent induced crystallization of 1,2,3,4(6),5-penta-O-acetyl-6(4)-O-[(1S)-10-camphor sulfonyl]-myo-inositol diastereomers associated via weak trifurcated C-H center dot center dot center dot O interactions - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (CrystEngComm, 2012)
The title compound produced three different types of solvent inclusion crystals having a conserved dimeric association via trifurcated C-H center dot center dot center dot O interactions between the diastereomers. These `dimeric' units are organized differently to produce three crystal types containing guest molecules. In type I and II, unit translated dimers created voids for guest inclusion, whereas in type III the guest sites were produced by helical association of dimers. Inclusion of dichloromethane gave two different types of crystals; however, we were unable to obtain unsolvated crystals of the title compound.

Synthesis and concomitant polymorphs of green fluorescence protein chromophore-anthracene-based fluorescent analogue - Mali, Bhupendra P.; Dabke, Niteen B.; Dash, Soumya R.; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Controlled variations in fluorescence properties hold significant promise for applications in optical sensors, bioimaging, and advanced display devices. However, constructing multicolor fluorescent systems remains a challenge. In this study, we demonstrate the development of multicolor fluorescence by generating polymorphs of a novel green fluorescent protein chromophore analogue, which exhibits distinct photoluminescence emissions in the solid state. The observed emission variations are attributed to differences in molecular conformation due to variations in pi-stacking interactions between the polymorphs. This offers a novel approach to designing materials with tunable fluorescence properties.

Switchable solid-state emission in GFP chromophore analogue cocrystals via competing AIE and ACQ pathways - Mali, Bhupendra P.; Dabke, Niteen B.; Sharma, Himanshu; Dash, Soumya Ranjan; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2026)
We present a crystal-engineering approach enabling switchable solid-state emission (green -> orange -> quenched) in GFP-chromophore analogue cocrystals. The coformer's electronic and supramolecular effect shifts the photophysical pathway: intramolecular CT in cocrystal-I (green) and cocrystal-III (quenched) and intermolecular CT in cocrystal-II, yielding orange emissions and highlighting cocrystallization's power for tunable luminophores.